Screening of Galician grapevine varieties by SNPs, phenotypic traits, and phytopathology - Díaz-Fernández, Ángela; Loureiro, M. Dolores; Pereira-Lorenzo, Santiago; Ibáñez, Javier; Díaz-Losada, Emilia (Frontiers in Plant Science, 2024)
The genetic erosion of the European grapevine diversity in the last century has promoted the conservation of varieties in germplasm banks to prevent their disappearance. The study of these varieties is peremptory as they would allow to diversify the wine market, as well as being a source of genes to face new pathogens or climate constraints. In this work, the grapevine varieties preserved in the 'Estación de Viticultura e Enoloxía de Galicia' (EVEGA) Germplasm Bank (Ourense, Spain) were widely characterized combining ampelography, ampelometry, agronomy and phytopathology. Also, genetic characterization was carried out through the analysis of 48 single nucleotide polymorphisms (SNPs). A Bayesian analysis based on the SNPs data was carried out to define the genetic structure of the EVEGA Germplasm Bank which allowed to differentiate two main Reconstructed Panmictic Populations (RPP), confirming previous results obtained based on microsatellite markers (SSRs). A great diversity between varieties was found for almost every parameter evaluated for ampelography, ampelometry, phytopatology, phenology and berry quality. A principal component analysis (PCA) performed with these phenotypical data allowed to discriminate among some groups of varieties included in different genetic populations. This study allowed to evaluate the grapevine diversity maintained in the EVEGA Germplasm Bank and characterize varieties of potential value for breeding programs of interest for the Galician viticulture.